Outcome of elective cemiplimab discontinuation in locally advanced or metastatic cutaneous squamous cell carcinoma patients achieving a complete remission - Fung, Tina; Samlowski, Wolfram (Frontiers in Oncology, 2026)
IntroductionCemiplimab treatment of patients with locally advanced or metastatic cutaneous squamous cell carcinoma induced rapid and deep tumor regressions. The majority of our cemiplimab-treated patients achieved a complete remission. It was not clear how long cemiplimab therapy should be continued in these patients, to prevent a subsequent relapse.Materials and MethodsWe identified cutaneous squamous cell carcinoma patients who were treated with cemiplimab via a computer database search. Individual patient records were then reviewed to identify patients who had achieved a radiographically or pathologically confirmed complete remission. Following elective treatment discontinuation based on our institutional standard, the outcomes of these patients were analyzed. ResultsComplete remissions were achieved in 15 out of 21 patients (71.4%) following cemiplimab treatment. The median treatment duration was only 5.3 ± 3.7 months (or 8.0 ± 3.6 doses of cemiplimab). With a median follow-up of 48.5 months following elective treatment discontinuation, only one of 15 patients experienced a delayed relapse. The other 14 patients have remained in a durable complete remission. DiscussionOur retrospective data review demonstrated that early elective cemiplimab discontinuation was both feasible, and safe. There was a low risk of relapse if patients achieve a radiologically or pathologically documented complete remission. We believe that decreases in the duration of cemiplimab treatment has the potential to reduce the risk of delayed checkpoint inhibitor toxicity, as well as decreasing treatment costs. Confirmation of our encouraging findings in a prospective clinical trial is recommended.